Book Notice - Dharma, Journal of (Journal of Dharma, 1999)
1. Sara Grant, Sankaracarya’s Concept of Relation, Delhi: Motilal Banarsidass, 1998, pp.xiv+205; Rs.295.00 (ISBN: 81-208-1597-1). 2. Robert E. Goodwin, The Playworld of Sanskrit Drama, Delhi: Motilal Banarsidass Publishers, 1998, pp.xxii+Zl Z; Rs.350.00 ISBN: 81-208-1589-0). 3. Roy W. Perrett, Hindu Ethics. A Philosophical Study, Honolulu: University of Hawaii, 1998 (Monograph No. 17. Society for Asian and Comparative Philosophy), pp.ix+l05; 28.00 (ISBN: 0-8248-2085-1). 4. Srinivasa Rao, Perceptual Error. The Indian Theories, Honolulu: University of Hawaii, 1998 (Monograph No. 16. Society for Asian and Comparative Philosophy), pp.xii+ 150; 20.00 (ISBN: 0-8248-1958-6). 5. RudolfV. d’Souza, Meeting in God-Experience. St. Teresa of Avila and the Bhagavadgita on Prayer, Anand: Gujarat Sahitya Prakash, 1999, pp. xv+ 186; Rs.60.00; 8.00. 6. Carlos G. Valles, S.J. Happy New Century! The Millennium of Hope, Anand: Gujarat Sahitya Prakash, 1998, pp.268; Rs.80.00; 10.00. 7. George Bishop, A Lion to Judah. The travels and Adventures of Pedro Paez; S.J., Anand: Gujarat Sahitya Prakash, 1998; pp.278; Rs.85.00; 12.00.